Effectiveness of Kumon Teaching Method for Academic Achievement of Children in Mathematics - Jamila Begum, Muhammad Maqsood Alam Bukhari, Aisha Akbar (PJE, 2023)
The experimental study was designed to investigate the effectiveness of Kumon method in comparison with traditional lecture method in the teaching of Mathematics to grade-5. Kumon is a math and reading enrichment program, which provides practice and instruction to each individual. This helps to think and work independently. The hypothesis of this study was that in Mathematics, Grade-5 students have no significant difference in their academic achievement treated by Kumon method and by traditional lecture method. The objective of the study was to determine the effectiveness of Kumon method for academic achievement of children in Mathematics. All grade-5 students of Fazaia inter colleges of Rawalpindi and Islamabad was the population. Cluster sampling technique was used. One of the three Fazaia colleges (junior section) was selected randomly. All grade-5 students of the selected cluster formed the sample of the study. Data was collected and analyzed by applying t-test and recommendations were given on the basis of findings of the study. This study shows that Kumon method is more effective for teaching mathematics to Grade 5 students in comparison with traditional lecture method and equally helpful in teaching mathematics effectively to boys and girls.